Efficiency of the program of P.E of students of teens - Кучер, В. О.; Григус, І. М. (Physical Education Theory and Methodology, 2012)
The purpose of the study — to identify effective ways to attract youngsters to take physical education. The study is based on secondary school adolescents. It was also attended by teachers of physical culture, class teachers, parents of pupils. Adolescents were divided into a control (n = 30) and primary (n = 30) groups, which were similar in age and physical development. As a result of the proposed program of physical education in view of features of adolescence, we see authentic growth of physical fitness and physical activity young core group at the end of the study. Introduction of the program had a positive effect on the body, had a preventive orientation, improved the cardiovascular and respiratory systems, contributed to the growth of the results at the time of training standards for physical development.